The Moderating Roles of Government in Poverty Reduction in Nigeria - Ukpata, Sunday Ijuo; Iyortsuun, Akuraun Shedrach; Angahar, Jacob Sesugh; Lukden, Rinret Winifred (Archives of Business Research, 2019)
This paper examined “The Moderating Roles of Government in Poverty Reduction in Nigerian” The paper critically evaluated the impact of government intervention in alleviating poverty in Nigeria.. It further addresses the issues of how these interventions programmes have proved to have been successful or have failed over time. The objective was to determine if there is statistically significant relationship between government expenditure on various poverty reduction programmes and economic growth in Nigeria. This we based our theoretical foundation on the Kuznet’s U Curve Hypothesis and the general income distribution theory to evaluate the link between inequality, poverty reduction and economic growth in Nigeria. In the methodology, our Model Specification was anchored on whether government programs has any significant influence on poverty reduction following the framework of Barro and Sala-i-Martin (1995) and Grootaert, Kanbbdur and Oh (1995) methods of analysis that uses a time subscript (t). We therefore modeled the relationship between poverty reduction and government programs through government expenditure on social intervention programs. The finding shows that there is no statistical significance between government expenditure and poverty reduction programs in Nigeria.